Ear infections in primary school children of south western Nigeria - Eziyi, Josephine A. E.; Oninla, Olumayowa A.; Salawu, Temitope O. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Prevalence of ear infections in primary school children in Nigeria is scarcely documented and available studies are mostly hospital based. The aim of this Community based study is to define the point prevalence of ear infections among school children. Methods: Using a multi- staged stratified sampling technique, 630 pupils aged 6-12years, attending Government owed primary schools in two local government areas in the South Western Nigeria were recruited for the application of a structured questionnaire, single examination and classification using their socioeconomic index. Results: Three hundred and seven (48.7%) were females and three hundred and twenty three (51.3%) were males. Chronic otitis media had the highest prevalence of 7.9%, followed by acute otitis media and otitis externa (3.2%) while otomycosis (1.6%) had the lowest. Majority of the infections were unilateral and more prevalent in the males. It was observed that all the ear infections were more prevalent in pupils from the low socioeconomic class although not statistically significant. Conclusions: These results shows that ear infections is still common in our primary schools and that socioeconomic status and sex of the pupils did not significantly affect the occurrence of these ear infections. There is a need to incorporate health education programme in schools to prevent ear infections and the attendant disabilities.